Morphological Changes in Ovaries in Rats with Experimental Polycystic Ovary - Chinara S. Zhylkichieva1 , Konstantin R. Nifontov2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Polycystic ovary syndrome is one of the important causes of infertility, metabolic syndrome. Complications of PCOS are a serious health hazard. The relevance of the study of morphological changes in the ovaries in rats is justified by the need to improve the treatment of PCOS. The experiment consisted in the fact that rats from the experimental group received testosterone for 7 days and were in constant artificial daylight for 60 days. As a result of histological examination of the ovaries in this group, multiple cysts, foci of fibrosis were found. Vaginal smears in rats from the experimental and control groups were collected and compared. The extracted ovaries of rats of the experimental and control groups were compared, the differences in colour according to Van Gieson X 100, haematoxylin-eosin X 40, haematoxylin-eosin X 100, B-G X 100 were analysed. Studies indicated oestrous cycle disturbance, hormonal changes in rats with experimental polycystic. The work can serve as material for further studies aimed at identifying fast and easily accessible methods for the diagnosis of metabolic syndrome predictors.